Strengthening the Capacity of Social Welfare Institutions for Service Quality to Orphans, the Elderly and the Disabled - Muchamad Suradji; Sauqi Futaqi; Moh. Hudi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The article was a community service result at the Al-Harokah Nahdhatul Ulama Social Welfare Institution (LKS-NU). It is a Social Welfare Institution with a focus on strengthening institutional capacity. The dedication of institutional management capacity at LKS NU Al Harokah used the Community-Based Participatory Research (CBPR) method. The results of this service showed that the strengthening of the institutional management capacity of the NU LKS had formed a separate management model. The strengthening activity also had a flow that started from the resources owned, the approach used, and the implementation process to the output and outcomes resulting from community service.